2007
DOI: 10.1111/j.1468-2508.2007.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Battleground States versus Blackout States: The Behavioral Implications of Modern Presidential Campaigns

Abstract: We examine the influence of "battleground" designation by presidential campaign strategists on the political activation and involvement of resource poor voters, particularly those in lower income brackets. We hypothesize that increased exposure to campaign stimuli may provide lower income voters in the contested states with an appreciable advantage over those in the "blackout" states by underwriting the costs associated with becoming engaged. Our findings show that the condition of living on contested electora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 38 publications
1
46
0
Order By: Relevance
“…In presidential years, the density of presidential advertising is also positively associated with campaign contacts. This confirms results from prior studies (Gimpel, Kaufmann, and Pearson-Merkowitz 2007;Huckfeldt et al 2007;Jacobson 2001;Wolak 2006) and suggests an indirect route of influence for concurrent campaigns. 14 To test whether the effects are due to Senate campaign tone, I rely on the percent of negative statements in the campaign newspaper and magazine articles collected and coded by Lau and Pomper (2004).…”
Section: Discussionsupporting
confidence: 93%
“…In presidential years, the density of presidential advertising is also positively associated with campaign contacts. This confirms results from prior studies (Gimpel, Kaufmann, and Pearson-Merkowitz 2007;Huckfeldt et al 2007;Jacobson 2001;Wolak 2006) and suggests an indirect route of influence for concurrent campaigns. 14 To test whether the effects are due to Senate campaign tone, I rely on the percent of negative statements in the campaign newspaper and magazine articles collected and coded by Lau and Pomper (2004).…”
Section: Discussionsupporting
confidence: 93%
“…Ideally, one would use CNN state rankings (Huber and Arceneaux 2007;Bergan et al 2005) or margins in state polls (Holbrook and McClurg 2005) prior to the start of the general election to gauge state competitiveness, but these measures are not available for the earlier elections in this study. Instead, I use the categorization of states created by Daron Shaw based on his interviews with presidential campaign consultants (Gimpel et al 2007;Hill and McKee 2005). Because Shaw was trying to analyze how a state's competitiveness affected candidates' allocation of resources, his measure captures how the candidates saw the electoral battlefield prior to the start of the general election (1999b, p. 896).…”
Section: Methodsmentioning
confidence: 99%
“…4 If political interest is higher in battleground states, one might expect higher levels of political discussion. Previous research is inconclusive on this point, however, with three studies finding no difference in the political interest of battleground and safe state residents (Wolak 2006;Benoit et al 2004;Lipsitz 2004) and one finding a sizeable difference (Gimpel et al 2007). The first three studies did find, however, that battleground state residents have higher levels of political knowledge, which is a significant predictor of political discussion.…”
Section: Which Forms Of Participation Should Be Affected By the Ec?mentioning
confidence: 96%
“…To this end, scholars have suggested that the effect of political competition measured at a lower level of aggregation (such as the neighborhood) on turnout is a result of social interaction across neighbors and the enforcement of social norms (Huckfeldt and Sprague 1995;Campbell 2006). On the other hand, the effect of political competition at a higher level of aggregation (such as the state) on turnout is a result of political mobilization and political stimuli, which both act to reduce the costs and increase the benefits of casting a vote (Rosenstone and Hansen 1993;Gimpel et al 2007). The difficulty in identifying these mechanisms results because it is entirely plausible for social norms especially in the form of political culture (Erikson et al 1993) to operate at higher levels of aggregation and for political mobilization to function at lower levels of aggregation (Smith and Zipp 1983).…”
Section: Defining the Political Contextmentioning
confidence: 99%